Heuristic and fuzzy scheduling synergy with knowledge acquisition of resource selection system development for home healthcare service - Thepparit Sinthamrongruk (2018)
Copyright © 2018 Inderscience Enterprises Ltd. Home healthcare service provides daily medical services at patients’ homes. The service aims to satisfy the patients’ requirements which must be done by qualified staff visiting them at the right time. This paper proposes a new framework integrating the heuristic search and fuzzy logic with knowledge acquisition to develop reliable and effective decision to match qualified staff to offer the service with the minimum cost, under preference consideration and feasible time-slots. The framework is designed based on the hierarchical approach dividing the system into two layers: high and low level. The high level is responsible for retrieving information, such as patients’ locations and operation cost while the lower level with fuzzy logic to estimate a set of the level of staff selection to create the service plan. Our empirical study of 40 medical tasks with eight carers shows that the framework has a potential to provide improved solutions than the original.